1,4,8,11,15,18,22,25-Octafluorophthalocyaninato Zinc (F8PcZn) - Crucius, Göran; Lyubimtsev, Alexey; Kramer, Markus; Hanack, Michael; Ziegler, Thomas (Synlett, 2012)
1,4,8,11,15,18,22,25-Octafluorophthalocyanato zinc (F8PcZn), which is not described in the literature up to date, was obtained from 3,6-difluorophthalonitrile in anhydrous DMF, DBU, and Zn(OAc)2 at 145 °C. 3,6-Difluorophthalonitrile was synthesized by a multistep procedure.
Keywords: 1,4,8,11,15,18,22,25-octafluorophthalocyanato zinc; glycosylated phthalocyanines; fluorinated phthalocyanines; 3,6-difluorophthalonitrile; phthalocyanato metals